DIGITAL CONTENT MARKETING DEVELOPMENT WITH A LEVEL UP STRATEGY FOR MSME’s IN INDONESIA “FROM LOCAL TO GLOBAL” - Wijaya, Carissa Vienna; Putri, Angely Olivia; Wijaya, Septihani Michella; Wijaya, Andi (International Journal of Application on Economics and Business, 2024)
Small and Medium Enterprises (MSMEs) in Indonesia seem to be experiencing challenges due to the rise of imported products circulating in the Indonesian market. However, the quality of MSME products is inconsistent. Not many buy local products or brands. Not all MSMEs in Indonesia have been digitized, which is why the development of digital marketing content with a level up strategy for MSMEs is still weak. We propose a Show with MSMEs strategy "From Local, For Global" and Integrated Marketing Communication suggested to be able to increase consumer awareness and interest by holding festivals and marketing bazaars. We believe this strategy can increase brand awareness, brand interest, and the brand image of MSMEs. We also develop a monitoring and control plan to measure the effectiveness of using the Key Performance Indicators. The research method than we used in this research are qualitative using case study.